2018
DOI: 10.1371/journal.pone.0202962
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing treatment of tauroursodeoxycholic acid to improve embryonic development after in vitro maturation of cumulus-free oocytes in mice

Abstract: Cumulus-free in vitro maturation (IVM) provides a powerful tool to manipulate immature oocytes, but IVM oocytes lead to poor development after fertilization. Supplementation of the culture medium with tauroursodeoxycholic acid (TUDCA), a bile acid, has been reported to improve the development of embryos derived from in vivo fertilized (IVF) embryos after in vitro culture (IVC) by attenuating endoplasmic reticulum stress. However, it remains unclear if TUDCA can improve development of IVM-IVF embryos. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Similarly, Song et al (2011) reported that addition of TUDCA reduced levels of Xbp1 splicing, transcription of the ER-stress-associated gene GRP78 , which codes for ATF6 , an α-mannidose-like protein that enhances ER degradation, and blastomere apoptosis in bovine SCNT embryos. In addition, TUDCA can reduce hyperosmolar-induced ER stress and ER-stress-induced apoptosis during oocyte development, and promote embryonic development in mouse embryos (Zhang et al, 2012a; Basar et al, 2014; Mochizuki et al, 2018). In contrast to previous studies, we applied TUDCA only during micromanipulation and 3 h after fusion and activation, not during the IVC stage, to enhance the in vitro development of the SCNT embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Song et al (2011) reported that addition of TUDCA reduced levels of Xbp1 splicing, transcription of the ER-stress-associated gene GRP78 , which codes for ATF6 , an α-mannidose-like protein that enhances ER degradation, and blastomere apoptosis in bovine SCNT embryos. In addition, TUDCA can reduce hyperosmolar-induced ER stress and ER-stress-induced apoptosis during oocyte development, and promote embryonic development in mouse embryos (Zhang et al, 2012a; Basar et al, 2014; Mochizuki et al, 2018). In contrast to previous studies, we applied TUDCA only during micromanipulation and 3 h after fusion and activation, not during the IVC stage, to enhance the in vitro development of the SCNT embryos.…”
Section: Discussionmentioning
confidence: 99%
“…TUDCA is a chemical chaperone known as an ER stress inhibitor that assists protein folding and suppresses ER stress (Xie et al, 2002;Lee et al, 2010). Several studies have shown that ER stress is inhibited when TUDCA is treated to embryo or cell in culture period (Zhang et al, 2012a,b;Yoon et al, 2014;Lin et al, 2015, Mochizuki et al, 2018. In addition, our previous study showed that when TUDCA is treated during the micromanipulation and activation processes of the SCNT embryo, Xbp1s and ER stress-associated genes are significantly reduced, thereby increasing the development and quality of SCNT embryos (Park et al, 2019).…”
Section: A B C Dmentioning
confidence: 99%
“…To relieve ER stress, ER stress inhibitors are added to the culture media. Tauroursodeoxycholic acid (TUDCA), a bile acid that acts as a potent chemical chaperone (Xie et al, 2002;Cortez and Sim, 2014), has been used to alleviate ER stress during in vitro oocyte maturation and/or embryo development (Song et al, 2011;Kim et al, 2012;Zhang et al, 2012;Yoon et al, 2014;Zhao et al, 2015;Mochizuki et al, 2018). Although the exact chaperoning mechanism of TUDCA is still unclear, it has been shown to prevent UPR malfunction and ameliorate ER stress in various cell types (Xie et al, 2002;Miller et al, 2007;Lee et al, 2010;Seyhun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%